Enough of this nonsense! Rape is rape : A Malaysian perspective - Janet Ann, Fernandez; Mohamad Nor, Azmawaty (Sage Journals, 2019)
There is an average of five rape cases reported in Malaysia on a daily basis. The problem lies not in the hands of an individual or a few misogynistic men but in society as a whole. It lies in the mind-set of the people and every one of us taking part in rape culture by endorsing rape myths. Rape myth acceptance within the Malaysian society encourages sexual assaults or sexual violence. Some of the popular rape myths are the victim’s choice of clothing, emotional reactions of victims, presence of physical injuries, rape happens between strangers, women lie about rape, and men cannot be raped. These most common rape myths are discussed and then debunked. Subsequently, the aftermath of rape is explained. Proactive actions against rape are also presented as many of the existing school-based programs against rape are lopsided as women are taught on how to avoid rape instead of men being taught to respect women and prevent rape. This article aims to serve as an eye-opener for Malaysian counselors, psychologists, educators, and society as a whole to build up their knowledge, skills, and experience when working or dealing with rape victims.